ANALISIS FAKTOR-FAKTOR KEPEMIMPINAN KEPALA SEKOLAH DASAR NEGERI DI KOTA PEKANBARU - Helmi Fitra; Mashadi Mashadi; Sumarno Sumarno (Universitas Riau, 2019)
This study aims to determine the dominant variables affecting the Principal Leadership of Primary Schools in Pekanbaru City especially Rumbai and Rumbai Pesisir District. Some of the variables in question were Achievement Motivation, Interpersonal Communication, Emotional Intelligence, Management Knowledge and Education Level. The population as a whole was 37 people and used as sample 32 people with determination of sample technique was Proportionate Stratified Random sampling. This research was conducted during September until November 2016. After the data of the research was analyzed, it was known that the two dominants independent variables affect the Leadership of Primary School Principal In Pekanbaru City namely:1) Emotional Intelligence 2) Education Level. The value of correlation coefficient between the variables of Emotional Intelligence (X3) to Principal Leadership (Y) 0.846 and the equation of simple regression line: Ŷ = 8.48 + 1.592X3. The correlation coefficient value between Headmaster Education (X5) toward Principal Leadership (Y) was 0,918 and simple regression line equation: Ŷ = -0.28 + 1.679X5. Emotional Intelligence (X3) and Education Level (X5) simultaneously affected the Principal Leadership (Y) was shown by the equation of the regression line to Y = -6.141 + 0.548X3 + 1.245X5, this means that at each increase of 1 unit of emotional intelligence ( X3) would be followed by an increase in principal leadership of ry1 0,548 if the level of education was controlled / constant and each increase of one-unit education level would be followed by increased principal leadership of 1,245 if emotional intelligence (X3) was controlled / constant. Viewed from the results of the correlation coefficient between the emotional intelligence variable of 0.846 was smaller than the Education Level of ry2 0.918.